Topographic features around Syowa Station as viewed from the gravity measurements -Some implications on the bedrock topography under the ice sheet- - Toshiyasu Nagao (National Institute of Polar Research, 1984)
The coefficients of the correlation between the reduced gravity anomaly and the bedrock height were calculated using gravity data in the Lutzow-Holm Bay region and the Mizuho Plateau, East Antarctica. A good positive relationship between the bedrock height and the reduced gravity anomaly was found on the sea ice and in the ice-free area of Lutzow-Holm Bay and in the ice-free area of the Yamato Mountains. On the contrary, the correlation between the reduced gravity anomaly and the bedrock height at gravity stations on the ice sheet whose ice thickness was measured by an ice radar survey showed a weak negative relationship. This fact may suggest that the determination of ice thickness by an ice radar on the ice sheet was inaccurate. The negative relationship between the reduced gravity anomaly and the bedrock height in the Mizuho Plateau means that the isostasy of this area is incomplete.